DOMESTICATION AND FOREIGNIZATION OF JAVANESE TERMS IN THE YEARS OF THE VOICELESS NOVEL - Juliana Juliana (Universitas Potensi Utama, 2019)
This research analyses domestication and foreignization strategies in translating the Javanese cultural words in Years of the Voiceless novel. The objective of this research was to obtain the most frequent strategies used in altering Javanese cultural words that influence the ideology used in the translation of the Years of the Voiceles novel. This research was a qualitative descriptive method. The data collection was by reading source and target texts with note taking techniques. The method of data analysis used content analysis with a comparison strategy of translated text in the novel and source text. The theory used to analyze the translation ideology was Venuti (2008) while the theory used to analyze Javanese cultural words was Newmark's theory of cultural categories. The result of the research showed that there was an influence of domestication ideology in the translation of the novel the years of the voiceless at the Javanese cultural words. The domestication was the dominant strategy used in translating Javanese cultural words in the Years of Voiceless novel. Therefore, It indicates the translator tend to maintain Javanese cultural words in ST into English culture words in TT.